Childhood, adolescent and young adult non‐Hodgkin lymphoma: current perspectives. (6th February 2019) - Cairo, Mitchell S.; Beishuizen, Auke
Summary: The 6th International Symposium on Childhood, Adolescent and Young Adult (CAYA) Non‐Hodgkin Lymphoma (NHL) was held in Rotterdam, Netherlands, 26–29 September, 2018. This summary manuscript is a perspective on the presentations from the plenary scientific sessions, including wellness and survivorship, B‐cell NHL, AYA lymphoma, translational NHL biology, lymphoma immunology, bone marrow transplantation and cell therapy, T/Natural Killer cell lymphoma, anaplastic large cell lymphoma, lymphoblastic lymphoma, novel lymphoma therapeutics and Hodgkin lymphoma. The symposium was attended by over 260 registrants from 42 different countries and included young, middle and senior investigators. Finally, the Angelo Rosolen, MD, Memorial Lecture was delivered by Alfred Reiter, MD.